Consumer Information Potpourri: Instructional and Operational Variability Among Passenger Vehicle Automated Systems. Issue 1 (January 2020) - Wright, Timothy J.; Svancara, Austin M.; Horrey, William J.
Even owners of the most advanced vehicles often have little understanding of the available in-vehicle technology. Accessible safety-critical information and standard instructional and operational components are potential routes to increase drivers' knowledge. This article presents a review of information obtained from automobile manufacturers' websites and operator manuals aimed toward passenger vehicle automated system consumers. This review revealed target areas for researchers, manufacturers, and policy makers to consider. Systems offering comparable functionality varied greatly in their nomenclature, type of feedback provided to drivers, and the accessibility of information about the systems. Also, information pertaining to systems limits was difficult to obtain.